Spatial Adaptation of Intellectual Disability Children in Special Needs School’s Dormitory in Yogyakarta - Eko Widodo; Syam Rachma Marcillia (Jurnal Kawistara, 2021)
Various studies have shown the important roles of spatial environment in shaping behavior and cognitive processes. However educational buildings are often not well designed for this specific purpose. This is especially the case with school dormitory for special need schools. The unavailability of school dormitory planning standards has an impact on variations in the building’s diverse physical settings. The daily activities carried out in the dormitory still found the use of one space for several types of activities. This has an impact on the density level, which further requires spatial adaptation that will be implemented by the residents. This study aims to find out spatial adaptation in three different physical settings of special needs school dormitories with the focus of observation being children with intellectual disabilities. The research method is based on a behavior mapping - place centered mapping approach. As the result, this research shows that there are variations in different spatial adaptations in responding to each of the physical setting conditions of the dormitory. The form of spatial adaptation involves changes in the physical setting and behavior, namely adjustment, reaction, and withdrawal. Furthermore, this type of spatial adaptation has different ways in achieving the ideal conditions of activities carried out in the physical setting of the dormitory.